2015
DOI: 10.1007/s11126-015-9397-8
|View full text |Cite
|
Sign up to set email alerts
|

Autovideography: The Lived Experience of Recovery for Adults with Serious Mental Illness

Abstract: Mental health services have been transforming toward a recovery orientation for more than a decade, yet a robust understanding of recovery eludes many providers, and consensus on a conceptual definition has yet to be reached. This article examines mental health consumers' lived experience of recovery and evaluates the usefulness and comprehensiveness of CHIME, a major framework conceptually defining recovery for adults with serious mental illness. Researchers partnered with a mental health association in a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Film methods facilitated capturing uniquely detailed descriptions of behavior, environment, interactions, sound, space, and movement. In one study, the authors described the power of film to capture what interviews alone could not:Videography is unique in its ability to capture voluminous details and nuances of interactions, events, and settings in real time—all of which can be reviewed multiple times to enable in-depth analysis unmatched by field notes, audio files, or transcripts alone (Petros, Solomon, Linz, DeCesaris, & Hanrahan, 2016, p. 416).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Film methods facilitated capturing uniquely detailed descriptions of behavior, environment, interactions, sound, space, and movement. In one study, the authors described the power of film to capture what interviews alone could not:Videography is unique in its ability to capture voluminous details and nuances of interactions, events, and settings in real time—all of which can be reviewed multiple times to enable in-depth analysis unmatched by field notes, audio files, or transcripts alone (Petros, Solomon, Linz, DeCesaris, & Hanrahan, 2016, p. 416).…”
Section: Resultsmentioning
confidence: 99%
“…Videography is unique in its ability to capture voluminous details and nuances of interactions, events, and settings in real time—all of which can be reviewed multiple times to enable in-depth analysis unmatched by field notes, audio files, or transcripts alone (Petros, Solomon, Linz, DeCesaris, & Hanrahan, 2016, p. 416).…”
Section: Resultsmentioning
confidence: 99%
“…Often these experiences are overlapping. Lived experience involvement has a variety of purposes; for example, the literature identifies that lived experience can both demonstrate why an intervention may or may not be effective or appropriate, as well as how that intervention works in everyday life [ 7 ]. However, in this sample, the most common experience was sharing a lived experience of suicide in a public forum with the perceived expectation that this will better inform audiences of what suicide is, and how suicide is experienced.…”
Section: Discussionmentioning
confidence: 99%
“…In the Australian context, active participation, where people share about the impacts of their life experiences, has long shaped programs and services in the health system [ 6 ]. Lived experience can both demonstrate why an intervention may or may not be effective or appropriate, as well as how that intervention works in everyday life [ 7 ]. Recently, this same movement has emerged in the suicide prevention sector, with the inclusion of lived experience now viewed as integral to most suicide prevention activities in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The CHIME framework has also been validated with consumer focus groups (Bird et al, 2014), and the study concluded that CHIME offered a defensible framework to guide clinical practice and research. Subsequent studies continued to report that CHIME matches consumers' descriptions of recovery (Petros, Solomon, Linz, DeCesaris, & Hanrahan, 2016) and systematic reviews of such descriptions (Stuart, Tansey, & Quayle, 2017). While newer processes have also been proposed in addition to CHIME, the original CHIME set of recovery processes was not challenged.…”
mentioning
confidence: 99%